Severe Multiorgan Failure Triggered by Infection in an Adult With Decades of Untreated Sickle Cell Disease: A Case Report - Sara Shahidi; Gisha Mohan (Clinical Case Reports, 2026)
ABSTRACT A 67‐year‐old man with decades of untreated sickle cell disease developed septic shock with multiorgan failure, splenic infarction, and marrow fibrosis; his genotype could not be confirmed. He recovered with intensive supportive care, with hydroxyurea initiated for long‐term disease modification, illustrating catastrophic infection‐triggered decompensation despite prolonged clinical quiescence.